The role of alternative polyadenylation in breast cancer - Qiao, Ping; Zhang, Caihong; Shi, Yingxu; Du, Hua (Frontiers in Genetics, 2024)
Breast cancer (BC), as a highly prevalent malignant tumor worldwide, is still unclear in its pathogenesis and has poor therapeutic outcomes. Alternative polyadenylation (APA) is a post-transcriptional regulatory mechanism widely found in eukaryotes. Precursor mRNA (pre-mRNA) undergoes the APA process to generate multiple mRNA isoforms with different coding regions or 3′UTRs, thereby greatly increasing the diversity and complexity of the eukaryotic transcriptome and proteome. Studies have shown that APA is involved in the progression of various diseases, including cancer, and plays a crucial role. Therefore, clarifying the biological mechanisms of APA and its regulators in breast cancer will help to comprehensively understand the pathogenesis of breast cancer and provide new ideas for its prevention and treatment.